2021
DOI: 10.1186/s12877-021-02227-5
|View full text |Cite
|
Sign up to set email alerts
|

Influence of comorbidities on functional outcomes in patients with surgically treated fragility hip fractures: a retrospective cohort study

Abstract: Background The incidence and number of fragility hip fractures are gradually increasing, resulting in a wide consumption of medical resources. Various factors affecting functional recovery in patients with fragility hip fractures are known, and comorbid diseases are one of them. The purpose of this study is to determine the effect of comorbidities on functional outcomes in patients surgically treated for fragility hip fractures, thereby contributing to the efficient distribution of medical reso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 44 publications
2
15
0
Order By: Relevance
“…Yoon et al [60] found that diabetes negatively affected a variety of functional outcomes, including not only K-IADL and also the FAC, EQ-5D, K-FRAIL, and geriatric depression scale related to depression. Lieberman et al [61] concluded that the rehabilitation outcome of diabetic patients was significantly worse than that of non-diabetic patients among older patients with hip fractures using the FIM scale.…”
Section: Discussionmentioning
confidence: 99%
“…Yoon et al [60] found that diabetes negatively affected a variety of functional outcomes, including not only K-IADL and also the FAC, EQ-5D, K-FRAIL, and geriatric depression scale related to depression. Lieberman et al [61] concluded that the rehabilitation outcome of diabetic patients was significantly worse than that of non-diabetic patients among older patients with hip fractures using the FIM scale.…”
Section: Discussionmentioning
confidence: 99%
“…HTN can influence pulmonary circulation, whereas liver disease and COPD can negatively influence the immune response to environmental pathogens in a hospital or community setting; all of these factors can increase the vulnerability of older patients to respiratory infection, especially during the acute period around surgery. These comorbidity factors can also negatively influence the functional recovery of older patients with fractures and indirectly cause acute respiratory problems when the recovery of the lower extremities is slow [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is noteworthy to note that 75% of patients do not die due to the pathology of the hip fracture itself, but rather as a consequence of a comorbidity prior to the injury [31]. Yoon et al have shown that dementia and DM have a signi cant effect on postoperative functional outcomes [32]. Anemia will increase hospital complications as well as hospitalization costs [33].…”
Section: Discussionmentioning
confidence: 99%